COVID-19 Investigational Treatments in Use Among Hospitalized Patients Identified Through the US Coronavirus Disease 2019–Associated Hospitalization Surveillance Network, March 1–June 30, 2020. (9th November 2020) - Acosta, Anna M; Mathis, Adria L; Budnitz, Daniel S; Geller, Andrew I; Chai, Shua J; Alden, Nisha B; Meek, James; Anderson, Evan J; Ryan, Patricia; Kim, Sue; Como-Sabetti, Kathryn; Torres, Salina; et al.
Abstract: Using a coronavirus disease 2019 (COVID-19)–associated hospitalization surveillance network, we found that 42.5% of hospitalized COVID-19 cases with available data from March 1–June 30, 2020, received ≥1 COVID-19 investigational treatment. Hydroxychloroquine, azithromycin, and remdesivir were used frequently; however, hydroxychloroquine and azithromycin use declined over time, while use of remdesivir increased. Abstract : Using data collected from a national surveillance network for COVID-19-associated hospitalizations, we describe inpatient COVID-19 investigational treatment use from March-June, 2020. Overall, hydroxychloroquine, azithromycin and remdesivir were used frequently. Over time, use of hydroxychloroquine and azithromycin declined, while remdesivir increased.